Pengukuran Beban Kerja Fisik dan Mental Operator Quality Control Kain Rajut di PT XYZ Dengan Metode Nasa TLX dan Work Load Analysis - Danu Adi Saputro; Anita Oktaviana Trisna Devi; Yunita Primasanti (Inovasi Kesehatan Global, 2025)
Each employee is assigned a specific workload, and each employee's workload must be appropriate and balanced with the physical and mental abilities of the worker receiving the workload. This study aims to determine the extent of the physical and mental workload of knitted fabric Quality Control (QC) operators at PT XYZ. Physical workload was measured using the Work Load Analysis (WLA) method, and mental workload was measured using the NASA Task Load Index (NASA TLX). The measurements show that the QC operators' physical workload reached 141.03%, placing them in the Overload category. Meanwhile, the mental workload measurement shows an average score of 70.22, categorizing them as high. Based on these results, several workload balancing efforts can be implemented. Physical workload balancing can be achieved by reducing the amount of work to be completed and adding one more member to the QC team. Meanwhile, mental workload balancing can be achieved by rewarding operators who successfully complete large quantities of fabric quality control work, and retraining them every six months is necessary.